2016
DOI: 10.1111/vec.12472
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of canine red blood cell quality after processing with an automated cell salvage device

Abstract: Although processing canine blood with this automated cell salvage device leads to slight changes in some properties of RBCs, most of these changes are comparable to changes seen in human blood after processing. Present data indicate that the use of this cell salvage device does not induce changes in canine RBC concentrate that would preclude its use for transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…A similar finding was demonstrated with a cell salvage device that also used 0.9% NaCl to wash canine erythrocytes. 46 Careful handling of these units, including using the least number of washes, would reduce risk of in vitro hemolysis. Our study also showed an increase in total Hgb between the final wash and the post‐transfusion temperature samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar finding was demonstrated with a cell salvage device that also used 0.9% NaCl to wash canine erythrocytes. 46 Careful handling of these units, including using the least number of washes, would reduce risk of in vitro hemolysis. Our study also showed an increase in total Hgb between the final wash and the post‐transfusion temperature samples.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of central pallor, increased RDW and MCV, and decreased MCHC with washing supports previous reports of human and canine RBC swelling after manual or automated RBC washing. 46 , 51 The cellular swelling during washing is widely considered to be secondary to build up of osmotically active substances (lactate, chloride, and 2,3‐DPG) intracellularly. 49 , 52 These osmotically active substances develop in RBCs during storage and, after washing, the extracellular osmolality decreases significantly depending on the washing media used, 53 , 54 resulting in an intracellular shift of fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reported complications of autotransfusion include haemolysis secondary to prolonged exposure to serosal membrane and mechanical injury during collection and re-infusion. 10,22,23 Haemolysis results in the release of free haemoglobin, which can lead to acute kidney injury. To minimise the risk of mechanical injury to the red blood cells, aspiration was performed gently using low-suction pressure to minimise cell damage during the retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve one year-old female Yucatan mini-pigs were included in the study with a median (min-max) weight of 46.9 (45.75-48.25) kg in the visceral model (n = 5) and 48 (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) kg in the cardiac model (n = 7). Each animal was individually identified by an ear tag (since a few days after birth) to guarantee traceability.…”
Section: Data On Animalsmentioning
confidence: 99%